Cyclone rotational drying of lignite based on particle high-speed self-rotation: Lower carrier gas temperature and shorter residence time. (1st April 2022) - Fu, Pengbo; Yu, Hao; Li, Qiqi; Cheng, Tingting; Zhang, Fangzheng; Yang, Tao; Huang, Yuan; Li, Jianping; Fang, Xiangchen; Xiu, Guangli; Wang, Hualin
Abstract: The lignite drying is the keys to its efficient and clean utilization, but the high energy consumption restricts the sustainable development of drying technology. In this study, based on the coupling centrifugal effect of high-speed self-rotation and revolution of particles in cyclone, low-energy consumption and high-efficiency lignite cyclone rotational drying was realized at a low carrier gas temperature (lower than 100 °C) and in a short residence time (less than 10 s). The influence of operating parameters and structure parameters on drying efficiency were studied, when the carrier gas temperature was 80 °C, the moisture content of lignite can be reduced from 45.1% to 15.2% after single-stage cyclone drying in a 75 mm diameter cyclone. Increasing the number of series stages and the diameter of the cyclone can further improve the drying efficiency. Compared with the evaporative drying, this new method can increase the drying rate and reduce the energy consumption. Graphical abstract: Image 1 Highlights: A novel cyclone rotational drying technology was developed for lignite dehydration. Moisture is removed through centrifugal action of lignite high-speed self-rotation. Cyclone drying can greatly increase the drying rate compared with fixed-bed drying. Efficient drying was realized at a low carrier gas temperature and in a short residence time. Moisture content can be reduced from 45.1% to 15.2% at a temperature of 80 °C.